Effect of Moderate-Intensity Acute Physical Activity on Decreasing Cortisol Levels in Obese Female - Cornelius Coli, Cornelius
Abstract Background: Obesity is an excessive fat accumulation within adipose tissue, which may caused by stress. The uncontrolled stress can increase cortisol hormone levels, thus increases appetite through ghrelin stimulation to cause obesity. Physical activity becomes a stressor, which depends on physical activity performed. Methods: This study was a true experiment with randomized pretest-posttest control group design. The study was conducted on 16 obese female which were divided into two groups, G1(n=8, control group) and G2 (n=8, moderate-intensity physical activity group). The subjects chosen by consercutive sampling technique. Moderate-intensity physical activity done by treadmill on 60-70% HRmax, and continuously performed for 30 minutes. Serum cortisol levels wasmeasured using enzyme-linked immunosorbent assay (ELISA) kit method. Results: The levels of cortisol on control group pretest (310.18±246.55) ng/mL and posttest (309.03±204.97) ng/mL were not significant different (P value: 0.992). Cortisol levels on moderate-intensity physical activity group pretest was 305.50±145.94 ng/mL dan posttest was 157.25±34.16 ng/mL, (P value: 0.058). Delta (Δ) cortisol levels on control group between pretest and posttest (–1.15±65.83) ng/mL, while on moderateintensity physical activity (–148.25±156.45) ng/mL, (P value: 0.028).